Refactoring with Microsoft Visual Studio 2010 : evolve your software system to support new and ever-changing requirements by updating your C♯ code base with patterns and principles /: evolve your software system to support new and ever-changing requirements by updating your C♯ code base with patterns and principles. (2010) - Unknown
No abstract available